Reporte de un caso clínico Sindrome de Rendu – Osler – Weber y Sîndrome Antifosfolipido: (Report of a clinical case Rendu – Osler – Weber Syndrome and Antiphospholipid Syndrome) (La U Investiga, 2024)
Rendu-Osler-Weber syndrome (HHT) is a vascular disorder characterized by the presence of telangiectasias and arteriovenous malformations. It is an autosomal dominant multisystem dysplastic vascular disorder. Antiphospholipid antibody syndrome is an autoimmune disease characterized by the formation of abnormal proteins in the blood called antiphospholipid autoantibodies (APs), which cause clots to form in the arteries and veins. Acute pulmonary embolism in a patient with arteriovenous malformation is a predisposing factor for potential complications. There are few case reports in which these two conditions were found at the same time, it is associated with an increased thrombotic risk due to iron deficiency. The clinical case of a 21-year-old patient with a history of HHT and findings of alveolar hemorrhage is presented, for which an immunological pathology is studied, finding positive results for APS.